Educational Inclusion By Conviction - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2020)
Inclusive education has begun to be addressed within the context of the broader international debate on “Education for All” (EFA), a debate launched at the World Conference held in 1990 in Jomtien, Thailand. From Jomtien until today , thinking has evolved from the almost symbolic presence of special educational needs in the initial documentation, towards the recognition that inclusion must be a fundamental principle of the EFA movement as a whole. Within this process, the contribution of the Salamanca Declaration on Special Educational Needs: Access and quality (Unesco, 1994) stands out, from which the concept of educational inclusion emerges strongly. Thereafter thescope and perspectives of inclusive education has been based on the idea that all children and young people have the right to a quality education with equivalent learning opportunities, regardless of their social and cultural background and their differences in skills and abilities (OIE -UNESCO, 20 08) .